A sea of biosynthesis: marine natural products meet the molecular age - Lane, Amy L. (2010)
The years 2000 through mid-2010 marked a transformational period in understanding of the biosynthesis of marine natural products. During this decade the field emerged from one largely dominated by chemical approaches to understanding biosynthetic pathways to one incorporating the full force of modern molecular biology and bioinformatics. Fusion of chemical and biological approaches yielded great advances in understanding the genetic and enzymatic basis for marine natural product biosynthesis. Progress was particularly pronounced for marine microbes, especially actinomycetes and cyanobacteria. During this single decade, both the first complete marine microbial natural product biosynthetic gene cluster sequence was released as well as the first entire genome sequence for a secondary metabolite-rich marine microbe. The decade also saw tremendous progress in recognizing the key role of marine microbial symbionts of invertebrates in natural product biosynthesis. Application of genetic and enzymatic knowledge led to genetic engineering of novel “unnatural” natural products during this time, as well as opportunities for discovery of novel natural products through genome mining. The current review highlights selected seminal studies from 2000 through to June 2010 that illustrate breakthroughs in understanding of marine natural product biosynthesis at the genetic, enzymatic, and small-molecule natural product levels. A total of 154 references are cited.